Preparation method of Fe-doped Bi2O2CO3 / Bi4TaO8Cl composite photocatalyst as well as product and application of Fe-doped Bi2O2CO3 / Bi4TaO8Cl composite photocatalyst

Through the preparation of Fe-doped Bi2O2CO3/Bi4TaO8Cl composite photocatalyst, using heterojunction and Fe element doping technology, the problems of low nitrogen oxide degradation efficiency and NO conversion to NO2 in existing photocatalysts under visible light were solved, and the problem of low nitrogen oxide degradation efficiency and NO conversion to NO2 was achieved. Efficiently remove NO and inhibit NO2 generation.

CN119236986APending Publication Date: 2025-01-03CHONGQING NORMAL UNIVERSITY
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411371764.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-29
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

The existing photocatalysts are easily converted into toxic nitrogen dioxide (NO) during the removal of nitric oxide (NO), resulting in environmental pollution and insufficient photocatalytic performance, especially in the low degradation efficiency of visible light.

Method used

The preparation method of Fe-doped Bi2O2CO3/Bi4TaO8Cl composite photocatalyst is adopted. Bi4TaO8Cl is combined with urea and Fe3Cl·6H2O through hydrothermal reaction to form a heterojunction and dopant with Fe element to collaborate the photocatalyst to improve the light absorption capacity and Charge separation efficiency.

Benefits of technology

It realizes efficient degradation of nitrogen oxides under visible light, while effectively inhibiting the conversion of NO to NO2, improving the removal rate and stability of the photocatalyst, and exhibiting excellent performance compared with other photocatalysts.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119236986A_ABST
    Figure CN119236986A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a Fe-doped Bi2O2CO3 / Bi4TaO8Cl composite photocatalyst as well as a product and application of the Fe-doped Bi2O2CO3 / Bi4TaO8Cl composite photocatalyst and belongs to the technical field of photocatalysis. Bi4TaO8Cl, urea and Fe3Cl. 6H2O are subjected to hydrothermal reaction to synthesize the Fe-doped Bi2O2CO3 / Bi4TaO8Cl composite photocatalyst, separation and transfer of photo-generated charges are accelerated, the carrier separation efficiency is improved, meanwhile, the visible light absorption efficiency is effectively improved through Fe doping, and the visible light absorption efficiency is improved. According to the present invention, the active free radical ROS is selectively generated, such that the ability of the photocatalytic degradation of NO to NO3 <-> is further improved while the conversion of NO to nitrogen dioxide NO2 is well inhibited, the performance is excellent, and the NO harmful gas can be efficiently degraded.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of photocatalysis, and in particular to a method for preparing a Fe-doped Bi2O2CO3 / Bi4TaO8Cl composite photocatalyst, and also to products prepared by the method and applications. Background Art

[0002] The rapid development of industry has brought more convenience to our lives, but also brought serious environmental pollution. x , where x = 1,2, NO accounts for about 95%) is an important precursor involved in the formation of secondary organic aerosols and ozone, leading to the current atmospheric environmental problems. In the past few decades, people have made a lot of efforts to find purification strategies for trace NO; photocatalytic oxidation technology stands out with its advantages such as easier use, lower cost and smaller environmental footprint. However, as an odd-electron molecule, NO exhibits excellent reactivity and therefore has multiple reaction pathways. When NO2 appears as the final product, environmental benefits are sacrificed, and the production of NO2 can cause serious respiratory diseases, decreased lung function and respiratory inflammation in the human body. Considering the multiple reaction pathways of NO and the toxicity of NO2, an effective strategy should be developed to inhibit the formation of NO2 during photocatalytic NO oxidation to ensure better environmental significance.

[0003] The common semiconductor photocatalysts currently have disadvantages such as high recombination rate of photogenerated carriers, low quantum efficiency, and small specific surface area, which result in insufficient photocatalytic performance. In view of the above shortcomings of existing catalysts, effective methods to better inhibit the conversion of nitric oxide (NO) to nitrogen dioxide (NO2) usually involve surface modification strategies of catalysts. The following are some of the main strategies:

[0004] (1) Precious metal loading. Precious metals (such as platinum Pt, palladium Pd, gold Au, etc.) are loaded onto the surface of the photocatalyst by physical adsorption or chemical deposition. Precious metals can act as electron trap centers, promote the separation of photogenerated electrons and holes, and improve the photocatalytic efficiency. In addition, they can also act as active sites to promote the adsorption and conversion of reactants. However, precious metals are expensive and may be at risk of loss, affecting the long-term stability of the catalyst; (2) Element doping. In the process of preparing photocatalysts, other atoms (such as non-metallic atoms nitrogen N, sulfur S, etc.; metal atoms iron Fe, cobalt Co, etc.) are introduced. Doping can adjust the band gap width and expand the light absorption range to the visible light region; improve charge transport and enhance photocatalytic activity; (3) Heterostructure construction. By combining two or more different materials to form a heterojunction, the separation of photogenerated electrons and holes can be promoted, the recombination of carriers can be reduced, and the photocatalytic efficiency can be improved; (4) Surface defect engineering. Defects such as oxygen vacancies and lattice defects are introduced on the surface of the photocatalyst. Defects can act as capture centers for photogenerated carriers, promote charge separation, and increase active sites.

[0005] Through the rational application of the above strategies, the conversion of NO to NO2 can be effectively inhibited while maintaining efficient removal of NO, thereby reducing the negative impact on the environment. In addition, multiple modifications are performed on the surface of the photocatalyst, such as constructing a heterojunction and combining element doping. The combination of multiple modification strategies can synergistically improve the photocatalytic performance. Bi4TaO8Cl, a bismuth-based semiconductor photocatalyst, is a new type of semiconductor photocatalyst with a special Sillén–Aurivillius perovskite crystal phase structure. This crystal structure can generate an internal electrostatic field between layers, thereby promoting the separation and transfer of photogenerated carriers. It is low in cost, non-toxic, and has a stable structure. However, the photocatalytic degradation efficiency of nitrogen oxides is still low. Therefore, we perform dual-functional modification on it, thereby obtaining efficient degradation of nitrogen oxides under visible light while effectively inhibiting the conversion of NO to NO2. Summary of the invention

[0006] In view of this, one of the objects of the present invention is to provide a method for preparing an Fe-doped Bi2O2CO3 / Bi4TaO8Cl composite photocatalyst; a second object of the present invention is to provide an Fe-doped Bi2O2CO3 / Bi4TaO8Cl composite photocatalyst prepared by the preparation method; a third object of the present invention is to provide the application of the Fe-doped Bi2O2CO3 / Bi4TaO8Cl composite photocatalyst in the degradation of nitrogen oxides.

[0007] In order to achieve the above object, the present invention provides the following technical solutions:

[0008] 1. A method for preparing a Fe-doped Bi2O2CO3 / Bi4TaO8Cl composite photocatalyst, wherein Bi4TaO8Cl is hydrothermally reacted with urea and Fe3Cl·6H2O to obtain Fe-doped Bi2O2CO3 / Bi4TaO8Cl.

[0009] Preferably, the mass ratio of Bi4TaO8Cl to urea and Fe3Cl·6H2O is 5:10:2.

[0010] Preferably, the hydrothermal reaction is carried out at 150° C. for 10 h.

[0011] Preferably, in the present invention, the mass of water in the hydrothermal reaction is equivalent to 120 times the mass of Bi4TaO8Cl.

[0012] Preferably, the Bi4TaO8Cl is prepared by grinding and mixing BiOCl with Ta2O5, Bi2O3, NaCl and KCl in a molar ratio of 1:2:3:10:10, heating to 700°C at a rate of 5°C / min and calcining for 3 hours to obtain a perovskite-type Bi4TaO8Cl bismuth tantalum oxyhalide compound having a thick nanosheet structure.

[0013] Preferably, the BiOCl is prepared by the following method: Bi(NO3)3·5H2O and KCl are used as raw materials, added to ethylene glycol and deionized water respectively, and then KCl aqueous solution is added dropwise to the ethylene glycol solution of Bi(NO3)3·5H2O, reacted for at least 2h, and centrifuged to obtain BiOCl.

[0014] 2. The Fe-doped Bi2O2CO3 / Bi4TaO8Cl composite photocatalyst prepared by the preparation method.

[0015] 3. Application of the Fe-doped Bi2O2CO3 / Bi4TaO8Cl composite photocatalyst in the degradation of nitrogen oxides.

[0016] The beneficial effects of the present invention are as follows: the present invention provides a preparation method of an Fe-doped Bi2O2CO3 / Bi4TaO8Cl composite photocatalyst, wherein BiOCl synthesized by a one-step method is used as a precursor, and a mixture consisting of Ta2O5, Bi2O3, NaCl and KCl is calcined into Bi4TaO8Cl by a molten salt method, which has a unique block structure; and urea and Fe3Cl·6H2O are added to prepare the Fe-doped Bi2O2CO3 / Bi4TaO8Cl composite photocatalyst by a hydrothermal method, and the Bi4TaO8Cl photocatalyst is modified with dual functions at the same time to form a synergistic modification effect.

[0017] The prepared catalyst can be used for photocatalytic removal of nitrogen oxides; the successful construction of Bi2O2CO3 / Bi4TaO8Cl-Fe visible light catalyst effectively utilizes the construction of heterojunction to promote the separation of photogenerated electrons and holes, reduce the recombination of carriers, and effectively utilizes Fe element doping to synergistically modify the photocatalyst, which enhances the absorption of visible light by Bi4TaO8Cl, forms more active free radicals, and further improves the photocatalytic degradation of NO by pure Bi4TaO8Cl. At the same time, it effectively inhibits the conversion of NO to NO2. Compared with the photocatalysts reported in other patents, the photocatalyst provided by the present invention has excellent performance. The present invention proposes a new photocatalyst Bi2O2CO3 / Bi4TaO8Cl-Fe with dual-functional surface modification and efficient degradation of NO harmful gas. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] In order to make the purpose, technical solution and beneficial effects of the present invention clearer, the present invention provides the following drawings for illustration:

[0019] Figure 1 XRD pattern of the Bi4TaO8Cl catalyst prepared in Example 1;

[0020] Figure 2 This is a SEM image of the Bi4TaO8Cl catalyst prepared in Example 1;

[0021] Figure 3 TEM and HRTEM images of the Bi4TaO8Cl catalyst prepared in Example 1;

[0022] Figure 4 This is a SEM image of the Bi2O2CO3 / Bi4TaO8Cl catalyst prepared in Example 2;

[0023] Figure 5 TEM and HRTEM images of the Bi2O2CO3 / Bi4TaO8Cl catalyst prepared in Example 2;

[0024] Figure 6 XRD pattern of the Bi2O2CO3 / Bi4TaO8Cl catalyst prepared in Example 2;

[0025] Figure 7 This is a SEM image of the Bi2O2CO3 / Bi4TaO8Cl-Fe catalyst prepared in Example 3;

[0026] Figure 8 TEM and HRTEM images of the Bi2O2CO3 / Bi4TaO8Cl-Fe catalyst prepared in Example 3;

[0027] Fig. 9This is the XRD pattern of the Bi2O2CO3 / Bi4TaO8Cl-Fe catalyst prepared in Example 3;

[0028] Fig.10 This is the XPS graph of Fe element of Bi2O2CO3 / Bi4TaO8Cl-Fe catalyst;

[0029] Fig.11 Photocurrent diagrams of Bi4TaO8Cl, Bi2O2CO3 / Bi4TaO8Cl and Bi2O2CO3 / Bi4TaO8Cl-Fe catalysts;

[0030] Fig.12 The activity diagram of photocatalytic NO removal of Bi4TaO8Cl, Bi2O2CO3 / Bi4TaO8Cl and Bi2O2CO3 / Bi4TaO8Cl-Fe catalysts for 30 minutes;

[0031] Fig.13 The photocatalytic NO2 production activity diagram of Bi4TaO8Cl, Bi2O2CO3 / Bi4TaO8Cl and Bi2O2CO3 / Bi4TaO8Cl-Fe catalysts in 30 minutes;

[0032] Fig.14 This is the activity diagram of Bi2O2CO3 / Bi4TaO8Cl and Bi2O2CO3 / Bi4TaO8Cl-Fe catalysts for long-term photocatalytic removal of NO;

[0033] Fig.15 The catalytic performance results under different Bi4TaO8Cl and urea mass ratios;

[0034] Fig.16 The catalytic performance results of Bi2O2CO3 / Bi4TaO8Cl-Fe were obtained by doping with different proportions of Fe. DETAILED DESCRIPTION

[0035] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments so that those skilled in the art can better understand the present invention and implement it, but the embodiments are not intended to limit the present invention.

[0036] Example 1. Preparation of pure Bi4TaO8Cl catalyst

[0037] Preparation of pure Bi4TaO8Cl catalyst, the specific method is as follows:

[0038] Weigh 2g Bi(NO3)3·5H2O and 0.2g KCl, add them into 100ml ethylene glycol and 30ml deionized water respectively, and stir them ultrasonically until dissolved; then add KCl aqueous solution dropwise to the mixed solution of Bi(NO3)3·5H2O and ethylene glycol, stir at room temperature for 2h, and centrifuge and dry to obtain BiOCl.

[0039] The obtained BiOCl and Ta2O5, Bi2O3, NaCl and KCl were added into an agate mortar in a molar ratio of 1:2:3:10:10, ground and mixed evenly, and then calcined in a muffle furnace. The temperature was set to about 700°C, the heating rate was 5°C / min, and after the insulation time was 3h, a bright yellow Bi4TaO8Cl precursor was obtained by filtration.

[0040] The phase analysis XRD diagram of the bright yellow precursor Bi4TaO8Cl provided in this embodiment is as follows Figure 1 As shown in the SEM images Figure 2 As shown, TEM and HRTEM images are as follows Figure 3 shown.

[0041] Example 2: Preparation of Bi2O2CO3 / Bi4TaO8Cl heterojunction with single functional surface modification

[0042] The preparation method of Bi2O2CO3 / Bi4TaO8Cl is as follows:

[0043] Weigh 2g Bi(NO3)3·5H2O and 0.2g KCl, add them into 100ml ethylene glycol and 30ml deionized water respectively, and stir them ultrasonically until dissolved; then add KCl aqueous solution dropwise to the mixed solution of Bi(NO3)3·5H2O and ethylene glycol, stir at room temperature for 2h, and centrifuge and dry to obtain BiOCl.

[0044] The obtained BiOCl and Ta2O5, Bi2O3, NaCl and KCl were added into an agate mortar in a molar ratio of 1:2:3:10:10, ground and mixed evenly, and then calcined in a muffle furnace. The temperature was set to about 700°C, the heating rate was 5°C / min, and after the insulation time was 3h, a bright yellow Bi4TaO8Cl precursor was obtained by filtration.

[0045] The obtained 0.5 g Bi4TaO8Cl and urea (Bi4TaO8Cl:urea mass ratio is 1:2) were added to 60 mL deionized water, stirred for 12 h, poured into a 100 mL hot water kettle, heated at 150 °C for 10 h, and centrifuged several times to obtain Bi2O2CO3 / Bi4TaO8Cl.

[0046] The SEM image of the Bi2O2CO3 / Bi4TaO8Cl catalyst synthesized in this example is as follows Figure 4As shown, the Bi2O2CO3 / Bi4TaO8Cl photocatalyst was subjected to HRTEM analysis. Figure 5 As shown, the 110 crystal planes corresponding to Bi2O2CO3 and Bi4TaO8Cl were found, proving that Bi2O2CO3 was successfully grown in situ on Bi4TaO8Cl. The XRD diagram of the phase analysis is shown in Figure 6 The results further confirm the successful construction of Bi2O2CO3 / Bi4TaO8Cl heterojunction.

[0047] Example 3: Preparation of Bi2O2CO3 / Bi4TaO8Cl-Fe Catalyst with Cooperatively Modified Bifunctional Surface

[0048] The preparation method of Bi2O2CO3 / Bi4TaO8Cl-Fe is as follows:

[0049] Weigh 2g Bi(NO3)3·5H2O and 0.2g KCl, add them into 100ml ethylene glycol and 30ml deionized water respectively, and stir them ultrasonically until dissolved; then add KCl aqueous solution dropwise to the mixed solution of Bi(NO3)3·5H2O and ethylene glycol, stir at room temperature for 2h, and centrifuge and dry to obtain BiOCl.

[0050] The obtained BiOCl and Ta2O5, Bi2O3, NaCl and KCl were added into an agate mortar in a molar ratio of 1:2:3:10:10, ground and mixed evenly, and then calcined in a muffle furnace. The temperature was set to about 700°C, the heating rate was 5°C / min, and after the insulation time was 3h, a bright yellow Bi4TaO8Cl precursor was obtained by filtration.

[0051] The obtained 0.5 g Bi4TaO8Cl, urea and Fe3Cl.6H2O (the mass ratio of urea, Bi4TaO8Cl and Fe3Cl.6H2O is 10:5:2) were added to 60 mL of deionized water, stirred for 12 h, poured into a 100 mL hot water kettle, and heated at 150 °C for 10 h to obtain Bi2O2CO3 / Bi4TaO8Cl-Fe.

[0052] The SEM image of the Bi2O2CO3 / Bi4TaO8Cl-Fe catalyst synthesized in this example is shown in Figure 7 As shown, the small particles of Bi2O2CO3 are loaded on the bulky large nanosheets of Bi4TaO8Cl; HRTEM analysis of the Bi2O2CO3 / Bi4TaO8Cl-Fe photocatalyst is performed, as shown Figure 8 As shown, it was found that the 110 crystal planes of Bi2O2CO3 and Bi4TaO8Cl were found, proving that Bi2O2CO3 was still successfully grown in situ on Bi4TaO8Cl. The XRD diagram of the phase analysis is shown in Fig. 9 The results further illustrate that the Fe doping is only ion doping and does not significantly change the phase structure composition of the Bi2O2CO3 / Bi4TaO8Cl heterojunction.

[0053] XPS analysis of the Fe element in the Bi2O2CO3 / Bi4TaO8Cl-Fe photocatalyst prepared in Example 3 revealed that the corresponding Fe 3+ and Fe 2+ The peaks of ions further confirm that Fe is doped in the Bi2O2CO3 / Bi4TaO8Cl heterojunction in the form of ions, such as Fig.10 shown.

[0054] The photocurrent analysis of the Bi4TaO8Cl, Bi2O2CO3 / Bi4TaO8Cl and Bi2O2CO3 / Bi4TaO8Cl-Fe photocatalysts showed that Bi2O2CO3 / Bi4TaO8Cl-Fe had a better carrier separation effect. Fig.11 shown.

[0055] Example 4: Study on the effect of catalyst on pollutant NO x Application in purification

[0056] Weigh 0.2g of Bi4TaO8Cl prepared in Example 1 and pour it into a culture dish with a diameter of 12cm, add an appropriate amount of ethanol, ultrasonically treat for 5min, evenly disperse, and then put it into a 60℃ oven and dry for 30min. Put the dried sample into the reaction tank of the nitrogen oxide instrument, and introduce nitrogen oxides at a concentration of ppb level; when the concentration in the nitrogen oxide analyzer is stable, turn on the 150W halogen tungsten lamp, react for 30min, and then turn off the light source;

[0057] Weigh 0.2 g of Bi2O2CO3 / Bi4TaO8Cl prepared in Example 2 and pour it into a culture dish with a diameter of 12 cm, add an appropriate amount of ethanol, ultrasonically treat for 5 minutes, evenly disperse it, and then put it into a 60°C oven and dry it for 30 minutes. Put the dried sample into the reaction tank of the nitrogen oxide instrument, and pass nitrogen oxides at a concentration of ppb level; when the concentration in the nitrogen oxide analyzer is stable, turn on the 150W halogen tungsten lamp, react for 30 minutes, and then turn off the light source.

[0058] Weigh 0.2g of Bi2O2CO3 / Bi4TaO8Cl-Fe prepared in Example 2 into a culture dish with a diameter of 12cm, add an appropriate amount of ethanol, ultrasonicate for 5min, evenly disperse, and then place in a 60℃ oven for drying for 30min. Place the dried sample in the reaction tank of the nitrogen oxide analyzer, and introduce nitrogen oxides at a concentration of ppb level; when the concentration in the nitrogen oxide analyzer is stable, turn on the 150W halogen tungsten lamp, react for 30min, and then turn off the light source.

[0059] (1) The catalytic performance of Bi4TaO8Cl prepared in Example 1 was tested under visible light conditions using an intermittent flow reactor. The specific test conditions were as follows: the initial NO concentration was 594 ppb, the amount of catalyst used was 0.2 g, the light source was a halogen tungsten lamp with a power of 150 W, a visible light filter was used, the flow rate ratio of NO to air was adjusted to 19:2400 by a flow controller, and NO and air were completely mixed. The performance and stability of removing NO under visible light were tested. Under 30 min of illumination, 83 ppb of NO harmful gas could be degraded, and the removal rate reached 14.37%. The output of toxic byproduct NO2 was 54 ppb (Table 1).

[0060] (2) The catalytic performance of Bi2O2CO3 / Bi4TaO8Cl prepared in Example 2 was tested under visible light conditions using an intermittent flow reactor. The specific test conditions were as follows: the initial NO concentration was 544 ppb, the amount of catalyst used was 0.2 g, the light source was a halogen tungsten lamp with a power of 150 W, a visible light filter was used, and the flow rate ratio of NO to air was adjusted to 19:2400 by a flow controller. NO and air were completely mixed, and the performance and stability of NO removal under visible light were tested. Under 30 minutes of illumination, 312 ppb of NO harmful gas could be degraded, with a removal rate of 57.45%. The production of toxic byproduct NO2 was 137 ppb, which had an excellent removal rate but produced additional byproducts (Table 1).

[0061] (3) The catalytic performance of Bi2O2CO3 / Bi4TaO8Cl-Fe prepared in Example 2 was tested under visible light conditions using an intermittent flow reactor. The specific test conditions were as follows: the initial NO concentration was 600 ppb, the amount of catalyst was 0.2 g, the light source was a halogen tungsten lamp with a power of 150 W, a visible light filter was used, and the flow rate ratio of NO to air was adjusted to 19:2400 by a flow controller. NO and air were completely mixed, and the performance and stability of NO removal under visible light were tested. Under 30 minutes of illumination, 408 ppb of NO harmful gas could be degraded, and the removal rate reached 63.94%. The output of toxic byproduct NO2 was 21 ppb, which had excellent removal rate and suppressed toxic byproduct NO2, and the long-term test results were more stable (Table 1).

[0062] The NO harmful gas degradation activity of the bright yellow precursor Bi4TaO8Cl, Bi2O2CO3 / Bi4TaO8Cl and Bi2O2CO3 / Bi4TaO8Cl-Fe catalysts provided in the embodiments of the present invention is shown in the figure Fig.12 As shown in Figure 2, the NO2 harmful gas production of Bi4TaO8Cl, Bi2O2CO3 / Bi4TaO8Cl and Bi2O2CO3 / Bi4TaO8Cl-Fe catalysts is as follows: Fig.13 As shown in the figure, the long-term photocatalytic NO removal activity of Bi2O2CO3 / Bi4TaO8Cl and Bi2O2CO3 / Bi4TaO8Cl-Fe is shown in the figure Fig.14 shown.

[0063] Table 1. Degradation efficiency of Bi4TaO8Cl and Bi2O2CO3 / Bi4TaO8Cl-Fe catalysts for NO harmful gas

[0064]

[0065] Example 5: Investigating the influence of different Bi4TaO8Cl:urea mass ratios on catalytic performance

[0066] Weigh 0.5 g of Bi4TaO8Cl prepared in Example 1 and urea (the mass ratio of Bi4TaO8Cl to urea is 1:1, 1:2, 1:3, and 1:4) and add them to 60 mL of deionized water. After stirring for 12 h, pour them into a 100 mL hot water kettle and heat at 150 °C for 10 h. Centrifuge several times to obtain Bi2O2CO3 / Bi4TaO8Cl heterojunctions with different Bi2O2CO3 loadings, which are named Bi2O2CO3 / Bi4TaO8Cl-1, Bi2O2CO3 / Bi4TaO8Cl-2, Bi2O2CO3 / Bi4TaO8Cl-3, and Bi2O2CO3 / Bi4TaO8Cl-4, respectively.

[0067] Referring to the method of Example 4, the degradation activity of Bi2O2CO3 / Bi4TaO8Cl heterojunctions with different Bi2O2CO3 loadings prepared in this example for NO harmful gas was tested. The results are as follows: Fig.15 As shown, when the mass ratio of Bi4TaO8Cl to urea is 1:2, the activity is the best, which is the optimal catalyst for this project.

[0068] Example 6: Investigating the effect of different ratios of Fe doping on the catalytic performance of Bi2O2CO3 / Bi4TaO8Cl-Fe

[0069] Weigh 0.5 g of Bi4TaO8Cl prepared in Example 1, urea and different proportions of Fe3Cl.6H2O (the mass ratio of Bi4TaO8Cl, urea and Fe3Cl.6H2O is 5:10:1, 5:10:2, and 5:10:3), add them into 60 mL of deionized water, stir for 12 h, pour into a 100 mL hot water kettle, heat at 150 ° C for 10 h, and centrifuge several times to obtain Bi2O2CO3 / Bi4TaO8Cl-Fe heterojunctions doped with Fe in different proportions, which are named Bi2O2CO3 / Bi4TaO8Cl-Fe-1, Bi2O2CO3 / Bi4TaO8Cl-Fe-2, and Bi2O2CO3 / Bi4TaO8Cl-Fe-3, respectively.

[0070] Referring to the method of Example 4, the degradation activity of NO harmful gas by Bi2O2CO3 / Bi4TaO8Cl-Fe heterojunctions prepared in this example with different Fe doping ratios was tested. The results are as follows: Fig.16 As shown, when the mass ratio of Bi4TaO8Cl, urea and Fe3Cl.6H2O is 5:10:2, the activity is the best, which is the optimal catalyst for this project.

[0071] The above-described embodiments are only preferred embodiments for fully illustrating the present invention, and the protection scope of the present invention is not limited thereto. Equivalent substitutions or changes made by those skilled in the art based on the present invention are within the protection scope of the present invention. The protection scope of the present invention shall be subject to the claims.

Claims

1. A method for preparing Fe-doped Bi2O2CO3 / Bi4TaO8Cl composite photocatalyst, characterized in that: Bi4TaO8Cl was hydrothermally reacted with urea and Fe3Cl·6H2O to obtain Fe-doped Bi2O2CO3 / Bi4TaO8Cl.

2. The method for preparing the Fe-doped Bi2O2CO3 / Bi4TaO8Cl composite photocatalyst according to claim 1, characterized in that: The mass ratio of Bi4TaO8Cl to urea and Fe3Cl·6H2O is 5:10:

2.

3. The method for preparing the Fe-doped Bi2O2CO3 / Bi4TaO8Cl composite photocatalyst according to claim 1 or 2, characterized in that: The hydrothermal reaction was carried out under the conditions of heating at 150° C. for 10 h.

4. The method for preparing the Fe-doped Bi2O2CO3 / Bi4TaO8Cl composite photocatalyst according to claim 1 or 2, characterized in that: The mass of water in the hydrothermal reaction is equivalent to 120 times the mass of Bi4TaO8Cl.

5. The method for preparing the Fe-doped Bi2O2CO3 / Bi4TaO8Cl composite photocatalyst according to any one of claims 1 to 4, characterized in that: The Bi4TaO8Cl is prepared by grinding and mixing BiOCl with Ta2O5, Bi2O3, NaCl and KCl in a molar ratio of 1:2:3:10:10, heating to 700°C at a rate of 5°C / min and calcining for 3 hours to obtain a perovskite-type Bi4TaO8Cl bismuth tantalum oxyhalide compound with a thick nanosheet structure.

6. The method for preparing the Fe-doped Bi2O2CO3 / Bi4TaO8Cl composite photocatalyst according to claim 5, characterized in that: The BiOCl is prepared by the following method: Bi(NO3)3·5H2O and KCl are used as raw materials, added into ethylene glycol and deionized water respectively, then KCl aqueous solution is added dropwise into the ethylene glycol solution of Bi(NO3)3·5H2O, reacted for at least 2 hours, and centrifuged and dried to obtain BiOCl.

7. An Fe-doped Bi2O2CO3 / Bi4TaO8Cl composite photocatalyst prepared by the preparation method according to any one of claims 1 to 5.

8. Use of the Fe-doped Bi2O2CO3 / Bi4TaO8Cl composite photocatalyst according to claim 6 in the degradation of nitrogen oxides.

Citation Information

Cited By

  • FeOOH / Bi4TaO8Cl heterojunction photo-Fenton catalyst as well as preparation method and application thereof

    CN120695853A

  • FeOOH / Bi4TaO8Cl heterojunction photo-Fenton catalyst, and preparation method and application thereof

    CN120695853B